Critical Reading Meets Digital Literacy: Understanding Scientific Works in a Transformative Age - Nuphanudin; Febriano Firmansyah; Maysya Tanaya Azzahra; Diandra Ekafirda Choirunnisa (Buletin Edukasi Indonesia, 2026)
This study aims to examine the relationship between critical reading and digital literacy in strengthening students’ ability to understand scientific works in the era of digital transformation. The rapid growth of digital information has changed the way students access, read, evaluate, and use academic sources. However, this development also creates challenges, especially in relation to misinformation, weak source evaluation, limited academic vocabulary, and passive technology use. This study employed a library research method by collecting and analyzing relevant books, journal articles, research reports, and academic documents on critical reading, digital literacy, scientific literacy, and digital ethics. The findings indicate that critical reading and digital literacy are mutually reinforcing competencies. Critical reading strengthens students’ ability to analyze arguments, evaluate evidence, distinguish facts from opinions, and interpret scientific texts reflectively. Meanwhile, digital literacy enables students to access, assess, manage, and use digital information ethically, creatively, and responsibly. The integration of both competencies supports deeper understanding of scientific works, enhances students’ critical thinking, and promotes responsible digital behavior. This study concludes that critical reading and digital literacy should be systematically integrated into educational curricula, teaching strategies, and academic literacy programs. Such integration is essential for preparing students to become critical, ethical, adaptive, and responsible learners in the digital age.